2010
DOI: 10.1371/journal.pgen.1000894
|View full text |Cite
|
Sign up to set email alerts
|

Allele-Specific Virulence Attenuation of the Pseudomonas syringae HopZ1a Type III Effector via the Arabidopsis ZAR1 Resistance Protein

Abstract: Plant resistance (R) proteins provide a robust surveillance system to defend against potential pathogens. Despite their importance in plant innate immunity, relatively few of the ∼170 R proteins in Arabidopsis have well-characterized resistance specificity. In order to identify the R protein responsible for recognition of the Pseudomonas syringae type III secreted effector (T3SE) HopZ1a, we assembled an Arabidopsis R gene T–DNA Insertion Collection (ARTIC) from publicly available Arabidopsis thaliana insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
196
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(211 citation statements)
references
References 78 publications
12
196
3
Order By: Relevance
“…1C; ref. 17). Similarly, in the zed1-6 knockout, PtoDC3000(hopZ1a) growth is similar to PtoDC3000(Ev) (Fig.…”
Section: Ref 1)mentioning
confidence: 57%
See 3 more Smart Citations
“…1C; ref. 17). Similarly, in the zed1-6 knockout, PtoDC3000(hopZ1a) growth is similar to PtoDC3000(Ev) (Fig.…”
Section: Ref 1)mentioning
confidence: 57%
“…We previously demonstrated that HopZ1a confers a growth advantage in the absence of ZAR1 when it is delivered by P. syringae pathovar cilantro (Pci0788-9), a strain closely related to a virulent strain of P. syringae pathovar maculicola (PmaES4326) (17). To determine whether HopZ1a would also confer a growth advantage in zed1, we infiltrated wild-type Col-0 or the zar1-1 or zed1-6 mutants with Pci0788-9 carrying hopZ1a or empty vector.…”
Section: Ref 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the same NLR can also interact with different host cofactors targeted by different pathogen effectors. In Arabidopsis, the NLR ZAR1 is required for the recognition of the HopZ1a effector from P. syringae (Lewis et al, 2010). ZAR1 is activated upon acetylation of the pseudokinase ZED1, by HopZ1a (Lewis et al, 2013).…”
Section: Discussionmentioning
confidence: 99%